GroEL of Lactobacillus johnsonii La1 (NCC 533) Is Cell Surface Associated: Potential Role in Interactions with the Host and the Gastric Pathogen Helicobacter pylori - Bergonzelli, Gabriela E. (American Society for Microbiology, 2006)
Heat shock proteins of the GroEL or Hsp60 class are highly conserved proteins essential to all living organisms. Even though GroEL proteins are classically considered intracellular proteins, they have been found at the surface of several mucosal pathogens and have been implicated in cell attachment and immune modulation. The purpose of the present study was to investigate the GroEL protein of a gram-positive probiotic bacterium, Lactobacillus johnsonii La1 (NCC 533). Its presence at the bacterial surface was demonstrated using a whole-cell enzyme-linked immunosorbent assay and could be detected in bacterial spent culture medium by immunoblotting. To assess binding of La1 GroEL to mucins and intestinal epithelial cells, the La1 GroEL protein was expressed in Escherichia coli. We report here that La1 recombinant GroEL (rGroEL) binds to mucins and epithelial cells and that this binding is pH dependent. Immunomodulation studies showed that La1 rGroEL stimulates interleukin-8 secretion in macrophages and HT29 cells in a CD14-dependent mechanism. This property is common to rGroEL from other gram-positive bacteria but not to the rGroEL of the gastric pathogen Helicobacter pylori. In addition, La1 rGroEL mediates the aggregation of H. pylori but not that of other intestinal pathogens. Our in vitro results suggest that GroEL proteins from La1 and other lactic acid bacteria might play a role in gastrointestinal homeostasis due to their ability to bind to components of the gastrointestinal mucosa and to aggregate H. pylori.